2019
DOI: 10.3389/fmicb.2019.02357
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide From Cysteine Desulfurase, Not 3-Mercaptopyruvate Sulfurtransferase, Contributes to Sustaining Cell Growth and Bioenergetics in E. coli Under Anaerobic Conditions

Abstract: Endogenous hydrogen sulfide (H2S), which is primarily generated by 3-mercaptopyruvate sulfurtransferase (3-MST) in Escherichia coli (E. coli) under aerobic conditions, renders bacteria highly resistant to oxidative stress. However, the biosynthetic pathway and physiological role of this gas under anaerobic conditions remains largely unknown. In the present study, we demonstrate that cysteine desulfurase (IscS), not 3-MST, is the primary source of endogenous H2S in E. coli under anaerobic conditions. A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…4B). This plausible scenario is further supported by recent results that SufS produces H 2 S via the persulfide intermediate under anaerobic conditions (Wang et al, 2019).…”
Section: Sufs and Sufu From F Islandicum Aw-1 Exhibit Cooperative Sulfur Transfer Activitysupporting
confidence: 74%
“…4B). This plausible scenario is further supported by recent results that SufS produces H 2 S via the persulfide intermediate under anaerobic conditions (Wang et al, 2019).…”
Section: Sufs and Sufu From F Islandicum Aw-1 Exhibit Cooperative Sulfur Transfer Activitysupporting
confidence: 74%
“…2A). Bacteria generally encode either 3MST or CBS/CSE, and it was recently demonstrated that L-cysteine desulfhydrases and cysteine desulfurases also contribute to H 2 S biogenesis in Escherichia coli (39,40). In addition, two groups recently reported the discovery of a glycyl radical enzyme from Bilophila wadsworthia that catalyzes C-S bond cleavage in the catabolism of tissueabundant taurine and the analogous alcohol isethionate (2hydroxyethanesulfonate) (41,42).…”
mentioning
confidence: 99%
“…Generation of H 2 S by CSE was measured using L-cysteine as the substrate in a spectrophotometric assay described previously [ 13 , 14 , 15 ]. The reaction of H 2 S production by CSE with lead acetate to form lead sulfide was monitored at 390 nm.…”
Section: Methodsmentioning
confidence: 99%